2019
DOI: 10.1155/2019/1296153
|View full text |Cite
|
Sign up to set email alerts
|

Plant Extracts in the Bone Repair Process: A Systematic Review

Abstract: Bone lesions are an important public health problem, with high socioeconomic costs. Bone tissue repair is coordinated by an inflammatory dynamic process mediated by osteoprogenitor cells of the periosteum and endosteum, responsible for the formation of a new bone matrix. Studies using antioxidant products from plants for bone lesion treatment have been growing worldwide. We developed a systematic review to compile the results of works with animal models investigating the anti-inflammatory activity of plant ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 82 publications
1
22
0
Order By: Relevance
“… 9 Studies have demonstrated the positive outcomes of plant extracts on bone healing through either of two mechanisms: osteoconductivity, which refers to the support for new bone ingrowth, or osteoinductivity, where a material stimulates cells to differentiate into osteogenic cells. 10 …”
Section: Introductionmentioning
confidence: 99%
“… 9 Studies have demonstrated the positive outcomes of plant extracts on bone healing through either of two mechanisms: osteoconductivity, which refers to the support for new bone ingrowth, or osteoinductivity, where a material stimulates cells to differentiate into osteogenic cells. 10 …”
Section: Introductionmentioning
confidence: 99%
“…In this context, EOs could become ideal candidates for this purpose. However, the results described in the literature are still limited [26], and further research is required for assessing their potential in orthopedic applications. Current studies involve the use of EOs for enhancing the regeneration of bone defects and preventing or treating osteoporosis and osteoarthritis and as bioactive compounds in bone scaffolds or implants for regenerative or antimicrobial purposes.…”
Section: Repair Phase Key Eventsmentioning
confidence: 99%
“…While bone regeneration is a complex process that allows the tissue to regain and maintain its structure and function with no scar formation, certain clinical situations require an acceleration of the process. Researchers have been focusing on identifying novel therapeutic agents that could aid the bone-healing process and understand the inflammatory mechanisms that modulate this process [25,26]. Since ancient times, nature has represented a major source of bioactive compounds that exhibit therapeutic properties [27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of medicinal plants for healing is the oldest form of medicinal practice of mankind [7]. Contemporary science has shown that some natural compounds have high anti-inflammatory, antioxidant and regenerative effects [8]. Brazil has great biodiversity (15-20% of the world's biodiversity), with about 60,000 varieties of plants, including some known for traditional use and others still not explored [9].…”
Section: Introductionmentioning
confidence: 99%